Kinerja Dinas Kesehatan Kabupaten Badung dalam Upaya Pemberantasan dan Penanggulangan Demam Berdarah Dengue (DBD) di Kecamatan Kuta Selatan - Ananda, Devi Gita; Yudartha, I Putu Dharmanu; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2023)
Background of the trouble on this look at is that instances of dengue fever in Badung Regency, specifically South Kuta, generally tend to range or range. The motive of this look at changed into to decide the overall performance of the Badung District Health Office in efforts to remove and manage dengue fever in South Kuta District. This studies makes use of a qualitative descriptive studies type. The outcomes of the studies carried out through researchers display that the overall performance of the Badung District Health Office in efforts to remove and manage dengue fever in South Kuta District is pretty accurate however desires improvement. Suggestions from this studies are the want for growing responsiveness to public court cases and the want for extra human resources. Keywords: Performance, Countermeasures, Public Head Office, Dengue Fever, South Kuta